Seed priming with plant waste extracts enhances maize drought tolerance in a genotype-specific manner - Wazeer, Hisham; Zeidan, Ahmad; Allevi, Jacopo; Pagano, Andrea; Dueñas, Conrado; Marocco, Adriano; Stagnati, Lorenzo; Doria, Enrico; Macovei, Anca (Frontiers in Plant Science, 2025)
Climate change poses major challenges to the agri-food sector, with drought episodes, defined as extended periods of limited water availability, representing one of the most damaging stress factors. While drought tolerance has been extensively studied during vegetative and reproductive stages, its effects on seed germination remain comparatively underexplored. This is particularly relevant for maize (Zea mays), a globally relevant staple crop whose productivity is highly sensitive to water deficit, making the identification of drought-tolerant varieties a high priority. Addressing this challenge requires sustainable agricultural practices. Plant-based biostimulants (PBs), derived from natural sources, are gaining attention for their ability to promote plant growth, enhance stress resilience, and reduce reliance on synthetic fertilizers, thus supporting both bioeconomy and environmental sustainability. Similarly, seed priming, a pre-sowing technique that improves germination efficiency, offers an additional strategy to strengthen crop resilience. In this study, 26 Italian maize genotypes were evaluated for their drought-tolerance potential. Biostimulants produced from plant waste by-products (red chicory and cauliflower extracts) were applied as seed priming agents and the germination performance under drought stress was monitored over a 14 days period. The germination behavior was evaluated by calculating several parameters, including germination percentage, speed, seedling growth, and stress tolerance index. In addition, reactive oxygen species (ROS) accumulation was quantified in the dry seeds of selected genotypes, alongside the expression of genes involved in ROS homeostasis and drought response. The obtained results reveal genotype-dependent responses to drought and demonstrate that priming treatments enhanced both drought tolerance and germination performance in several maize genotypes. This study emphasizes the value of genetic diversity and highlights the potential of seed priming with plant-based biostimulants as a sustainable strategy within the framework of circular bioeconomy and climate-resilient agriculture.